Analisis Sistem Informasi Akuntansi Penggajian Pada CV ABC di Jawa Tengah: Payroll Accounting Information System Analysis on CV ABC in Central Java - Pramesti, Wahyu; Trijayanti, Desi (Journal of Accounting Science, 2019)
This research was conducted at CV ABC which is engaged in the furniture industry. In managing the payroll system this company is still less effective. It can be seen from several salary payment activities to employees who still often make mistakes in the process of calculating salaries and employee attendance records. In addition, in the process of paying salaries to employees, they often experience late payments. The purpose of this study is to analyze the payroll accounting information system in the company which is expected to help resolve the problems faced by the company. The research method used in this study is a qualitative descriptive research method. The thing that will be done by the researcher is to describe the use of payroll accounting system on CV ABC. The conclusion of this study is that the payroll system on CV ABC is already good because it has used a computerized system. The internal control in the payroll process is still weak because there are still division of tasks and responsibilities of each part that is unclear, namely there is a double duty and interdependence in working tasks, besides that supervision is still lacking for activities that should be routinely checked or corrected.